Tingkat Pengetahuan Masyarakat Terhadap Tindakan Penggunaan Antibiotik Tanpa Resep Dokter - Madania Madania; A. Mu’thi Andy Suryadi; Fika Nuzul Ramadhani; Andi Makkulawu; Dizky Ramadani Putri Papeo (Journal Syifa Sciences and Clinical Research, 2022)
Antibiotics is a subtance that can kill or weaken an organism such as bacteria, parasite, or fungi.  The use of antibiotics always triggers a problem, such as the use of it without any medical prescription. It sometimes happens caused by some factors such as the lack of people’s knowledge concerning the consumption of antibiotics. This research aims at investigating the correlation between the respondent’s characteristics toward knowledge, attitude, and action. Also, it is to investigate the correlation between knowledge and attitude toward the consumption of antibiotics without medical prescription. The research design applies analytical observation with cross sectional approach. The research subjects are 96 respondents selected by purposive sampling technique. The research instrument is questionnaires consisting of questionnaire of knowledge, attitude, and action. The method of data analysis is multiple correlation. Findings reveal that the people’s level of knowledge is still low obtaining 47,7% of score, the people’s attitude is categorized negative (supporting the consumption of antibiotics without medical) obtaining 54,2%, the people’s action categorized not appropriate obtaining 57,3%, there is correlation between education and job toward knowledge, attitude, and action (p0,05), there is no correlation between age and sex toward knowledge, attitude, and action (p0,05), and there is a correlation between knowledge and attitude toward action (p=0,000).